Outcomes of ADHD Symptoms in Late Adolescence: Are Developmental Subtypes Important?. Issue 1 (January 2020) - Murray, Aja Louise; Booth, Tom; Auyeung, Bonnie; Eisner, Manuel; Ribeaud, Denis; Obsuth, Ingrid
Objective: Substantial individual variation exists in the age of onset and course of ADHD symptoms over development. We evaluated whether, within this variation, meaningful developmental subtypes can be defined.Method: Using growth mixture modeling in a community-based sample ( N = 1, 571), we analyzed ADHD symptom trajectories based on measures taken at ages 7, 8, 9, 10, 11, 13, and 15 years. We evaluated whether those showing developmental trajectories characterized by later onsets versus early onsets differed in terms of mental health and behavioral outcomes in late adolescence (age 17 years).Result: The late onset category was best conceptualized as a milder subtype than early onset. The former was, however, more similar in outcomes to the latter than to the unaffected category, suggesting that later onsets are still associated with impairment.Conclusion: Considering diagnoses for those affected by ADHD symptoms but who do not meet current age of onset criteria may be important for ensuring that they receive appropriate support.